Reconceptualizing overall visitor satisfaction as an average of satisfaction with attributes - Taplin, Ross (Croatian National Tourist Board, 2016)
© 2016 Cognizant, LLC.The tourism, management, and marketing literature debates the meaning of consumer satisfaction with a product or service, including methods for identifying factors influencing satisfaction. This methodological article adds to this literature by reconceptualizing overall satisfaction with a product or service as a weighted average of the satisfaction with its attributes or components. This is particularly valuable for researchers and managers investigating which attributes of a product or service have the greatest influence on overall satisfaction. Existing models are reconceptualized in this way, new models are introduced, and an equality F test is proposed as a goodness-of-fit test. This reconceptualization is shown to have considerable merit in terms of fit to data and interpretability of results, whereas the equality F test provides a previously unavailable test of whether important determinants of satisfaction have been modeled inadequately or whether important attributes have been omitted altogether from the visitor survey. The new methodology is illustrated using a survey of 322 visitors at an Australian metropolitan zoo.